Prevalence and grade of diabetic peripheral neuropathy among known diabetic patients in rural Uganda - Munyambalu, Dalton Kambale; Hildago, Idania; Bafwa, Yves Tibamwenda; Lagoro, Charles Abonga; Sikakulya, Franck Katembo; Vahwere, Bienfait Mumbere; Dafiewhare, Ephraim; Martinez, Lazaro; Charles, Fardous Abeya (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Diabetic Peripheral Neuropathy (DPN) is the most common complication of Diabetes Mellitus (DM). Approximately fifty percent of diabetic patients are estimated to develop diabetic peripheral neuropathy depending on disease duration and diabetic control. Early diagnosis of DPN will avoid complications whose the most debilitating is non-traumatic low limb amputation with significant problems for the patients, psychologically, socially and economically. There is a paucity of literature on this condition from rural Uganda. This study aimed to deliver the prevalence and classification of Diabetic Peripheral Neuropathy among DM patients in Rural Uganda. Methods: A cross-sectional study which recruited 319 known DM patients was conducted in Outpatient clinic and Diabetic Clinic at Kampala International University-Teaching Hospital between December 2019 and March 2020. Questionnaires were used to obtain clinical and sociodemographic data, neurological exam was done to assess the DPN and blood sample was collected from each participant (Random/Fasting Blood Glucose, Glycosylated Hemoglobin). Data was analyzed using STATA version 15.0. Results: The sample size was of 319 participants. The mean age of study participants was 59.4±14.6 years and females were 197(61.8%). The prevalence of DPN was at 65.8% (210/319), (95%, CI 60.4-70.9); from which 44.8% had mild Diabetic Peripheral Neuropathy, 42.4% had moderate Diabetic Peripheral Neuropathy and 12.8% had severe Diabetic Peripheral Neuropathy. Conclusion: The prevalence of DPN at KIU-TH was higher and its stage might have a negative impact on the progression of Diabetes Mellitus. Therefore, clinicians should consider neurological examination as a routine during assessment of all DM patients especially in rural areas where resources and facilities are often limited so that complications related to Diabetic mellitus will be prevented.